2018
DOI: 10.3390/d10030055
|View full text |Cite
|
Sign up to set email alerts
|

Assemblage and Species Threshold Responses to Environmental and Disturbance Gradients Shape Bat Diversity in Disturbed Cave Landscapes

Abstract: Ecological thresholds represent a critical tipping point along an environmental gradient that, once breached, can have irreversible consequences for species persistence and assemblage structure. Thresholds can also be used to identify species with the greatest sensitivity to environmental changes. Bats are keystone species yet are under pressure from human disturbances, specifically landscape and cave disturbances (i.e., reduced forest cover, urbanization, hunting, tourism). We compared bat assemblages across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 55 publications
4
14
0
Order By: Relevance
“…Decomposing forest communities into taxonomic groups showed that this pattern might be related to an increase in bird, bat and plant species that are either tolerant to management or promoted by it. We hypothesize that higher forest management intensities correspond to stands having a more open canopy, which allows better foraging options for bats and more light availability for understory plants, as found in other studies 25 , 50 , 51 . Forest management might also affect bird species communities in mature managed forests, by increasing stand-level structural heterogeneity 13 , 27 , 52 , 53 , and creating suitable conditions for species that demand more open conditions (early successional specialists) 54 .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Decomposing forest communities into taxonomic groups showed that this pattern might be related to an increase in bird, bat and plant species that are either tolerant to management or promoted by it. We hypothesize that higher forest management intensities correspond to stands having a more open canopy, which allows better foraging options for bats and more light availability for understory plants, as found in other studies 25 , 50 , 51 . Forest management might also affect bird species communities in mature managed forests, by increasing stand-level structural heterogeneity 13 , 27 , 52 , 53 , and creating suitable conditions for species that demand more open conditions (early successional specialists) 54 .…”
Section: Discussionsupporting
confidence: 54%
“…In order to assess the variability across the taxonomic groups and tree-related microhabitats in community‐level change‐points, we ran TITAN both when considering all species together, and for each taxonomic group separately 22 . In line with previous applications of the method 50 , we only considered indicators having purity > 0.95 and reliability > 0.7. Purity quantifies the proportion of change-point response directions (positive or negative) among bootstrap replicates that agree with the observed response.…”
Section: Methodsmentioning
confidence: 99%
“…Foliage roosting species are affected by a reduction in roosting opportunities whereas cave-dwelling species are affected by both disturbance at the roost and greater commuter costs as foraging habitats are fragmented [38,82]. Body mass is positively correlated with resilience to disturbance, whereas smaller species that emit higher peak frequencies responded negatively [67,83]. Mean body mass of the species recorded in our study was twice as high in the extralimital agriculture (26.44 g) than in the core zone (13.11 g; Table 2), however this does not consider the relative abundance of each species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the interpretation of extinction risk requires caution as factors may act in synergy and we could not fully account for the intensity of human-induced threats 76 . This is particularly challenging to pinpoint in the context of cave biota, in which even a single disturbance may alter the entire sensitive biota and ecosystems, and as such events cannot be identified vulnerability (e.g accessibility) must be used as an indicator 31,50,77 . Furthermore, the degree of expertise required for bat and cave studies means less data is available compared to other taxonomic groups 74,78 .…”
Section: Conservation Decision Making Depends On the Clear Delineation Between What Ismentioning
confidence: 99%